Cognitive reserve and AβI-42 in mild cognitive impairment (Argentina-Alzheimer’s disease neuroimaging initiative) - Harris, Paula (2015)
Background: The purpose of this study was to investigate the relationship between cognitive reserve and concentration of Aβ1-42 in the cerebrospinal fluid (CSF) of patients with mild cognitive impairment, those with Alzheimer’s disease, and in control subjects. Methods: Thirty-three participants from the Argentina-Alzheimer’s Disease Neuroimaging Initiative database completed a cognitive battery, the Cognitive Reserve Questionnaire (CRQ), and an Argentinian accentuation reading test (TAP-BA) as a measure of premorbid intelligence, and underwent lumbar puncture for CSF biomarker quantification. Results: The CRQ significantly correlated with TAP-BA, education, and Aβ1-42. When considering Aβ1-42 levels, significant differences were found in CRQ scores; higher levels of CSF Aβ1-42 were associated with higher CRQ scores. Conclusion: Reduced Aβ1-42 in CSF is considered as evidence of amyloid deposition in the brain. Previous results suggest that individuals with higher education, higher occupational attainment, and participation in leisure activities (cognitive reserve) have a reduced risk of developing Alzheimer’s disease. Our results support the notion that enhanced neural activity has a protective role in mild cognitive impairment, as evidenced by higher CSF Aβ1-42 levels in individuals with more cognitive reserve.